Nanosecond response perovskite quantum dot light-emitting diodes with ultra-high resolution for active display application - Qingkai Zhang; Kaiyu Yang; Chengyu Luo; Zhihan Lin; Weiguo Chen; Yongsheng Yu; Hailong Hu; Fushan Li (Light: Science & Applications)
Abstract Perovskite quantum dots light-emitting diodes (PeLEDs) have been developed for next-generation high resolution display applications. However, the hindered charge injection and massive charge trapping due to the insulating and defective surface of quantum dots (QDs) usually lead to a slow rise in electroluminescence (EL) response, which makes it challenging to realize ultra-high refresh rate displays with nanosecond response. Herein, an ionic liquid 1-Butyl-3-methylimidazolium Trifluoromethanesulfonate ([BMIM]OTF) was used to enhance the crystallinity and reduce the surface area ratio of QDs, which effectively decreases defect state and injection barrier at the interface. Therefore, the rise time of EL response with steady-state is successfully reduced by over 75%. We further reduce the capacitance effect by decreasing the light-emitting unit area. Thus, ultra-high resolution (9072 pixel per inch) PeLEDs with light-emitting pixel size of 1.3 μm were realized, achieving a brightness exceeding 170,000 cd/m2 and an external quantum efficiency up to 15.79%. Moreover, it achieves nanosecond ultrafast response time under steady-state, which is the fastest response time of PeLEDs reported so far. Our work represents the most advanced performance of ultra-high-resolution PeLEDs, and provides in-depth insights into the mechanism of improving their response speed, showing significant potential in high refresh rate active display application.